2010
DOI: 10.1038/ngeo983
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary membrane lipids recycled by deep-sea benthic archaea

Abstract: Deep-sea sediments harbour a vast biosphere. Archaea—one of the three domains of life1—are prevalent in marine environments2, 3, 4, 5, and comprise a significant fraction of the biomass in marine sediments6. Archaeal membranes are well characterized, and are comprised of a glycerol backbone and a nonpolar isoprenoid chain. However, the ecology of sedimentary archaea remains elusive, because it is difficult to grow them in the laboratory. Here, we trace the fate of 13C-labelled glucose added to marine sediments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 29 publications
9
77
1
2
Order By: Relevance
“…MCG are likely to access substrates that are physically or chemically recalcitrant. This conclusion is in agreement with findings from previous literature (Biddle et al, 2006;Lipp et al, 2008;Takano et al, 2010;Webster et al, 2010;Lliró s et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…MCG are likely to access substrates that are physically or chemically recalcitrant. This conclusion is in agreement with findings from previous literature (Biddle et al, 2006;Lipp et al, 2008;Takano et al, 2010;Webster et al, 2010;Lliró s et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…The present study focused on benthic foraminifera, because they are known to consume substantial amounts of organic carbon on the deep-sea floor (Moodley et al 2002, Gooday et al 2008). Total uptake rates of 13 C-labeled substrates by archaea were not quantified since (1) the archaeal biomass estimation based on the concentration of lipid biomarkers has some variables and (2) the rates of incorporation of 13 C to archaeal membrane lipids were highly heterogeneous between glycerol and isoprenoid (Takano et al 2010), making it difficult to estimate total archaeal uptake rate using a single membrane lipid biomarker. …”
mentioning
confidence: 99%
“…com/articles/ suppl/ m431p011_supp.pdf). Subsamples (15 cm 3 ) of the sediments were used for the analysis of bulk organic matter and archaeal membrane lipid analysis (Takano et al 2010). These samples were kept frozen at -80°C and then freeze-dried.…”
mentioning
confidence: 99%
“…In situ production was suggested by Hoefs et al (2002), who found apparently high preservation efficiency of C 16 and C 18 fatty acids which was attributed, in part, to bacterial in situ production in the sediment. However, evidence has emerged that this in situ production of IPL-GDGTs may effectively be quite low (Takano et al, 2010;Lin et al, 2012;Xie et al, 2013), except for in settings with high activity such as sulfate-methane transition zones, and thus unlikely to cause a substantial change in IPL GDGT distributions.Here, we investigate the long-term (~10 kyr) effects of post-depositional oxygen exposure on the distribution of IPL GDGTs and CL GDGTs in the f-turbidite of the MAP (Buckley and Cranston, 1988). We analyzed CL GDGT and IPL GDGT concentrations and the respective TEX 86 , BIT and MBT/ CBT values of a fresh sediment core MAP-4 from the unoxidized f-turbidite, the overlying oxidized hemipelagic sediments, and the overlying unoxidized e-turbidite.…”
Section: Introductionmentioning
confidence: 99%